Ornamental plantings of Arbutus unedo L. facilitate colonisations by Charaxes jasius (Linnaeus, 1767) in Madrid province, central Spain - Juan Pablo Cancela; Sasha Vasconcelos (Nota Lepidopterologica, 2019)
The distribution of butterfly species is limited by availability of larval host plants growing in suitable climatic conditions. The Two-tailed Pasha, Charaxes jasius (Linnaeus, 1767), is a Mediterranean butterfly with only sporadic historical records in Madrid, Spain’s most central province, where the host plant is uncommon and winters are colder than in most parts of the butterfly’s range. We show the first evidence of juvenile stages of the species in two towns of north-central Madrid and compile records of C. jasius from Madrid over the past four decades. Our results suggest that, in the absence of widespread host plants, C. jasius is using suburban ornamental plantings of its host plant to colonise a region which may be becoming more climatically suitable.